The Importance of Innovation in Learning Facilities to Support Student Competency Development - Harianto, Budi (Management Department Universitas Islam Negeri Sumatera Utara, 2024)
Innovative learning environments play a critical role in fostering key competencies in higher education. The research was conducted using a survey method involving the participation of alumni representatives from all study programs at UINSU. Based on the findings from 490 samples alumni, it is known that the emphasis on learning and learning aspects contribute significantly to predicting the perception of competence possessed by alumni (Y). However, learning facilities do not significantly contribute to Y. Based on the findings, facilities such as laboratories, libraries, and classrooms were deemed statistically insignificant in affecting competency development. Instead, learning methods, student engagement, and teaching quality played a more dominant role. Some of the causes of insignificant learning facilities are underutilization of resources, traditional teaching, and access barriers. The recommended improvement is innovation in evolve to become more integrated with teaching methods, fostering active, experiential, and collaborative learning. Universities should focus not only on building modern facilities but also on ensuring these facilities are effectively utilized to support competency development. Keywords: Leaning facilities innovation, Competency development, Higher studies